Hepatitis C and not Hepatitis B virus is a risk factor for anti-tuberculosis drug induced liver injury. Issue 1 (December 2015) - Kim, Wan; Lee, Sang; Lee, Chang; Kim, Hong; Ha, Chang; Kim, Hyun; Kim, Tae; Jung, Woon; Lee, Ok; Hong, Jeong; You, Hyun; Cho, Hyun
Abstract Background The risk of anti-tuberculosis (TB) drug-induced liver injury (DILI) in patients with chronic viral hepatitis (CVH) is not clear. The aim of this study was to investigate incidence and risk factors associated with TB DILI in CVH and non-CVH patients. Methods Retrospectively, a total of 128 CVH patients who received anti-TB medication from January 2005 to February 2014 were reviewed. Among these, 83 patients had hepatitis B virus (HBV), 41 patients had hepatitis C virus (HCV) and 4 patients were dual hepatitis B and hepatitis C virus co-infected (HBV + HCV) with 251 non-CVH patients who received anti-TB medication selected as the controls. There were no human immunodeficiency virus co-infected patients. Risk factors for DILI were analyzed using cox regression analysis. Results The incidence of DILI was significantly higher in the HCV group (13/41 [31.7 %], p < 0.001) and HBV + HCV groups (3/4 [75.0 %], p = 0.002) compared to the control group (25/251 [10.0 %]). The incidence of transient liver function impairment in the hepatitis B virus group was higher than in the control group (18/83 [21.7 %] vs. 27/251 [10.8 %]p = 0.010), but not in DILI (11/83 [13.3 %] vs. 25/251 [10.0 %], p = 0.400). In total patients, HCV, HBV + HCV co-infection, older age, and baseline liver function abnormality were independent factors of DILI. Conclusions It is recommended to carefully monitor for DILI in patients with HCV or HBV/HCV co-infection, older age, and baseline liver function abnormality.